Globalisation and Conflict: Evidence from Sub-Saharan Africa - Carolyn Chisadza; Manoel Bittencourt (Revue Internationale de Politique de Développement)
Stephen Pinker (2011) advances that various forms of violence, such as homicide, rape, torture and conflict, have decreased over time because of the following historical shifts in society: the pacification process, civilising process, humanitarian and rights revolutions and extended periods of peace. We regard these shifts as processes encompassed in globalisation and investigate the effects of globalisation on conflict, one of the forms of violence Pinker (2011) discusses. We use panel data from 46 sub-Saharan African countries dated 1970 to 2013 and find that increased globalisation significantly reduces conflict. The results suggest that the historical shifts removed boundaries between territories and created incentives that discouraged hostility. Furthermore, we find that social globalisation, which is associated with the historical shifts, drives the results. The influence of social interactions through increased migration, commerce and access to information encourages tolerance and raises the opportunity cost of conflict. We also disaggregate conflict into intrastate and interstate and find that the intrastate conflict is significantly reduced by globalisation processes as compared to interstate conflict.